2003
DOI: 10.1086/380750
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Evolution of the Outflow Collimation in Very Young Stellar Objects

Abstract: We present Very Long Baseline Array proper-motion measurements of water masers toward two young stellar objects (YSOs) of the W75 N star-forming region. We find that these two objects are remarkable for having a similar spectral type, being separated by 0Љ .7 (corresponding to 1400 AU), and sharing the same environment, but with a strikingly different outflow ejection geometry. One source has a collimated, jetlike outflow at a 2000 AU scale, while the other has a shell outflow at a 160 AU scale expanding in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
121
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 107 publications
(131 citation statements)
references
References 27 publications
10
121
0
Order By: Relevance
“…Statistical properties of the spatial distribution of water masers Using VLBA data of three epochs of water maser observations toward the SFRs Cepheus A and W75 N (Torrelles et al 2001b(Torrelles et al , 2003, we compute two-point spatial correlation functions of maser spots in the following subregions: R5 in Cepheus A, and VLA 1 and VLA 2 in W75 N. In each of these subregions, a few hundred maser spots were detected with an S/N ≥ 10 in each one of the three epochs (see Table 1). The uncertainties in the values of these functions are mainly due to position uncertainty of maser spots, which is more significant toward small separations (represented by the error bar sizes shown in Figures 1-3).…”
Section: Resultsmentioning
confidence: 99%
“…Statistical properties of the spatial distribution of water masers Using VLBA data of three epochs of water maser observations toward the SFRs Cepheus A and W75 N (Torrelles et al 2001b(Torrelles et al , 2003, we compute two-point spatial correlation functions of maser spots in the following subregions: R5 in Cepheus A, and VLA 1 and VLA 2 in W75 N. In each of these subregions, a few hundred maser spots were detected with an S/N ≥ 10 in each one of the three epochs (see Table 1). The uncertainties in the values of these functions are mainly due to position uncertainty of maser spots, which is more significant toward small separations (represented by the error bar sizes shown in Figures 1-3).…”
Section: Resultsmentioning
confidence: 99%
“…Although the scaling of the magnetic field in water maser is due to shocks, Vlemmings (2006Vlemmings ( , 2008 empirically showed that even water masers with number densities up to 10 11 cm −3 follow this relation, even if in non-masing gas of similar densities the magnetic field strengths are likely lower due to ambipolar diffusion. Hence, from the magnetic field strengths, we can determine the number density of the cloud where the H 2 O masers arise by the relation B ∝ n 0.47 .…”
Section: |mentioning
confidence: 99%
“…Therefore, observational signatures of rotating disks around O-type forming stars are essential to progressing in our understanding of the mass-accretion process and to constraining theoretical models of high-mass star formation. In this context, one excellent diagnostic tool of gas kinematics within 10-1000 AU from YSOs is provided by multiepoch very long baseline interferometric (VLBI) observations of interstellar masers Goddi et al , 2011Matthews et al 2010;Moscadelli et al 2007Moscadelli et al , 2011Moscadelli et al , 2013Sanna et al 2010a,b;Torrelles et al 2003Torrelles et al , 2011. Among different molecular masers, CH 3 OH is particularly interesting, because it is exclusively associated with high-mass star formation and provides an excellent probe of accretion.…”
Section: Introductionmentioning
confidence: 99%